2018
DOI: 10.1108/ajim-03-2018-0067
|View full text |Cite
|
Sign up to set email alerts
|

Politicians’ use of Facebook during elections

Abstract: Purpose The purpose of this paper is to understand the use of Facebook by Israeli party leaders during an election period by examining four elements: the type of Aristotelian language of persuasion; the level of online engagement measured by three different types of feedback: likes, comments and shares; the use of personalization elements as engagement strategies; and the vividness features used in the post (text, photographs and video). Design/methodology/approach All of the posts from the Facebook pages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 61 publications
1
8
0
1
Order By: Relevance
“…The current study uses quantitative and qualitative content analysis as a tool for conducting a comparative examination of the social media activities of government ministries and authorities in Israel. Previous studies conducted in Israel used this method to examine information distribution and presentation on social media by political leaders and parties (Bar-Ilan et al , 2015; Bronstein et al , 2018) and local governments (Lev-On and Steinfeld, 2015). As it was presented earlier, similar studies have focused on the relationship between government authorities and social media (Chen et al , 2020; Gintova, 2019; Gu et al , 2020; Lovari and Bowen, 2020; Silva et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study uses quantitative and qualitative content analysis as a tool for conducting a comparative examination of the social media activities of government ministries and authorities in Israel. Previous studies conducted in Israel used this method to examine information distribution and presentation on social media by political leaders and parties (Bar-Ilan et al , 2015; Bronstein et al , 2018) and local governments (Lev-On and Steinfeld, 2015). As it was presented earlier, similar studies have focused on the relationship between government authorities and social media (Chen et al , 2020; Gintova, 2019; Gu et al , 2020; Lovari and Bowen, 2020; Silva et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Israel's ministries and government authorities have fully implemented social media in their work plans and strategies, as they mostly prefer Facebook as their primary tool for communication and citizenry dialogue (Yavetz and Aharony, 2020). Research in the field of online government in Israel has, however, largely focused on political information related to parties, candidates and elections campaigns (Aharony, 2012; Bar-Ilan et al , 2015; Bronstein et al , 2018; Lev-On and Haleva-Amir, 2016; Markowitz-Elfassi et al , 2019). Another emerging research topic focuses on local and municipality authorities' activities on social media in the Israeli context (Lev-On and Steinfeld, 2015, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concretely, studies focusing on visual rhetoric revealed that the appeal to ethos on YouTube political videos, measured as the credibility of the message source, was the most credible appeal, followed by logos and pathos in the 2008 US presidential campaign (English et al, 2011). On the contrary, studies focused on verbal rhetoric (Bronstein et al, 2018;Johnson, 2012) found that pathos is as relevant as ethos to persuade. Johnson (2012) specifically found that the motivation behind most of Romney's tweets during the 2012 US presidential campaign was to establish logical connections and to build credibility (ethos).…”
Section: Digital Persuasion In Social Mediamentioning
confidence: 99%
“…Johnson (2012) specifically found that the motivation behind most of Romney's tweets during the 2012 US presidential campaign was to establish logical connections and to build credibility (ethos). Bronstein et al (2018) revealed that pathos was the most important element in all the Facebook posts of Israeli political leaders during the 2015 general election, with the aim of creating an affective bond with the audience and the public.…”
Section: Digital Persuasion In Social Mediamentioning
confidence: 99%
“…Kutatásom eredményeinek jelentős része ezekben a más kontextusokban folytatott vizsgálatokban megerősítést nyert, a legnagyobb eltérések éppen az eredeti hipotézisemnek ellentmondó mobilizációs tartalmak kapcsán bontakoztak ki. Itt pozitív, negatív hatások és nem szignifikáns eredmények egyaránt megjelentek(Bronstein et al, 2018;Heiss et al, 2018; Keller & Kleinen-von Königslöw, 2018; Stetka et al, 2018).A módszertan leírásánál a kutatás egyéb korlátjaira is kitértem. Röviden visszautalva az ott leírtakra, limitálja a kutatás érvényességét, hogy az algoritmusok, a fizetett hirdetések és az aktivisták hatásának kiszűrésére nem vállalkozhatott.…”
unclassified